Public Exposure and Response to Environmental Sanitation Messages on Adamawa Broadcasting Corporation (ABC) Radio Yola, Adamawa State - Umar, Gaya Kaltume; Yerima, Abel; Graham, Abel Billy (ALSYSTECH Journal of Education Technology, 2026)
This study examined public exposure to and responses toward environmental sanitation messages broadcast by Adamawa Broadcasting Corporation (ABC) Radio within Yola Metropolis, Adamawa State. Using a survey research design, a sample of 399 respondents was drawn from a population of 371,038 residents based on Taro Yamane’s formula. The findings reveal relatively low levels of exposure to sanitation-related messages aired on ABC Radio. While the credibility of these messages was perceived as moderate, the study identified limited behavioural compliance with recommended sanitation practices, including proper waste disposal and participation in community clean-up efforts. The weak response was attributed to infrastructural deficits such as inadequate waste disposal facilities, irregular waste collection, and weak enforcement of existing sanitation regulations. The study concludes that message exposure alone is insufficient to drive behavioural change without supporting environmental infrastructure and enforcement mechanisms. It recommends that ABC Radio increase the frequency and appeal of its environmental programmes by integrating more interactive and engaging formats, such as talk shows, street vox pops, drama skits, and listener call-in segments, to enhance public engagement and responsiveness.